2009
DOI: 10.4161/cbt.8.9.8105
|View full text |Cite
|
Sign up to set email alerts
|

NFκB activity and transcriptional responses in human breast adenocarcinoma cells after single and fractionated irradiation

Abstract: Radiotherapy is considered mandatory for breast cancer patients undergoing conservative surgery and for women at high risk of recurrence. However, relapse due to radio-resistance affects the success of radiotherapy. Ascertaining the fractionated radiation (FIR) modulated molecular targets is important to make tumors more susceptible to molecular targeted therapy. Accordingly, we investigated the (i) expression of 84 genes representing six functional pathways; (ii) NFkappaB DNA binding activity and; (iii) expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…NF-jB is a transcription factor that promotes the expression of genes involved in inflammatory and antiapoptotic response [37][38][39][40]. It has been demonstrated that NF-jB plays a critical role in development and progression of breast cancer [41][42][43]. Furthermore, it has been proposed that BRCA1 acts as a co-activator of NF-jB [44].…”
Section: Discussionmentioning
confidence: 99%
“…NF-jB is a transcription factor that promotes the expression of genes involved in inflammatory and antiapoptotic response [37][38][39][40]. It has been demonstrated that NF-jB plays a critical role in development and progression of breast cancer [41][42][43]. Furthermore, it has been proposed that BRCA1 acts as a co-activator of NF-jB [44].…”
Section: Discussionmentioning
confidence: 99%
“…38,41 Irradiation also can activate NF-kB survival transcription factor via degradation of IkBa. 42,43 The radiation-induced activation of HIF-1a and NF-kB has been proposed as dominant governor triggering radioprotection of tumor vessels and critical determinant of radioresistance. ING4 can potentially inhibit the transcriptional activity of NF-kB and HIF-1a leading to the inhibition of production of proangiogenic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, AdVING4 almost completely eliminated the increased Cox-2 and survivin induced by ionizing radiation. It has been shown that ionizing radiation can enhance the transcriptional activity of NF-kB 42,43 and HIF-1a 38 and positively modulate the expression of downstream genes Cox-2 47,48 and survivin. 49,50 It has also been reported that ING4 can efficiently suppress the activity of NF-kB and HIF-1a.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is considered mandatory for glioblastoma patients [2] . However, the development of radioresistance remains a significant therapeutic hindrance and limits the effectiveness of ionizing radiation (IR) in treating patients with glioma [1,3] .…”
Section: Introductionmentioning
confidence: 99%